Evaluation of clinical and endoscopic toxicity after external beam radiotherapy and endorectal brachytherapy in elderly patients with rectal cancer treated in the HERBERT study. Issue 3 (March 2018) - Rijkmans, E.C.; van Triest, B.; Nout, R.A.; Kerkhof, E.M.; Buijsen, J.; Rozema, T.; Franssen, J.H.; Velema, L.A.; Laman, M.S.; Cats, A.; Marijnen, C.A.M.
Abstract: Introduction: The HERBERT study evaluated a high-dose-rate endorectal brachytherapy boost (HDREBT) after EBRT in medically inoperable/elderly patients with rectal cancer. The response-rates are promising but not without risk of toxicity. The current analysis provides a comprehensive overview of patient reported, physician reported and endoscopically observed toxicity. Material and methods: A brachytherapy dose finding study was performed in 38 inoperable/elderly patients with T2-T4N0-1 rectal cancer. Patients received EBRT (13 × 3 Gy) followed by three weekly HDREBT applications (5–8 Gy). Toxicity was assessed via three methods: patient and physician (CTCAEv3) reported rectal symptoms and endoscopically. Wilcoxon's signed rank test, paired t-test and Spearman's correlation were used. Results: Patient reported bowel symptoms showed a marked increase at the end of EBRT and two weeks after HDREBT. Acute grade 2 and 3 proctitis occurred in 68.4% and 13.2% respectively while late grade 2 and ≥3 proctitis occurred in 48% and 40%. Endoscopic evaluation mainly showed erythema and telangiectasia. In three patients frank haemorrhage or ulceration occurred. Most severe toxicity was observed 12–18 months after treatment. Conclusion: For elderly patients with rectal cancer, definitive radiotherapy can provide good tumour response but has a substantial risk of toxicity. The potential benefit and risks of a HDREBT boost above EBRT alone must be further evaluated.